An Empirical Analisis of Firm Value: A Case Study of Indonesian Real Estate Company (International Journal of Psychosocial Rehabilitation, 2020)
The firm value is still a current issue that is often discussed by various groups in the world of the economy, including corporate owners, investors, governments, economic observers, and researchers in various studies and financial literacy of the company. The question is, how do companies increase the firm value of their companies? And what factors determine the firm value in the field of property and real estate in Indonesia? This study was conducted to analyze whether capital expenditure, leverage, agency cost, and profitability have an influence on firm value on the Indonesia Stock Exchange in the property and real estate business in 2013-2018. All variables proposed in this study were formed based on literature studies. a total of 65 companies as a population and a sample of 39 companies. The panel data regression method is chosen by the researcher in this research. Panel data regression analysis results show that only the capital expenditure variable does not have an impact on firm value, while other independent variables have an impact on firm value. Based on testing that has been done, it is expected to be a source of information for investors before investing. For companies, the results of this study become a reference for improving financial performance to increase firm value.